Thoracic outlet syndrome in a postoperative cervical spondylotic myelopathy patient: A case report. Issue 11 (March 2019) - Wang, Xiao-Tao; Yao, Min; Zhong, Ming; Wang, Yong-Jun; Shi, Qi; Cui, Xue-Jun
Abstract: Rationale: Thoracic outlet syndrome (TOS) is a rare disease that presents with neurogenic and vascular symptoms similar to those of cervical spondylosis. However, making the diagnosis of TOS can be challenging due to a lack of standardized objective confirmatory tests. Patient concerns: A 66-year-old man presented with neck, supraclavicular, and right shoulder pain as well as numbness and weakness in the right arm after surgery to correct cervical spondylotic myelopathy (CSM). Diagnosis: Magnetic resonance imaging confirmed the diagnosis of CSM. He was diagnosed with TOS based on the manifestations and examination findings. Interventions: After surgery for CSM, nonoperative management was provided. Outcomes: The patient reported pain relief and improving sensation in the shoulder and supraclavicular region. Lessons: Based on this case and the reviewed literature, to optimize the diagnosis and treatment of CSM, clinicians should consider preoperative differential diagnosis to preliminarily exclude it.